2022
DOI: 10.18805/lrf-684
|View full text |Cite
|
Sign up to set email alerts
|

Role of Osmotic Regulation and Cryoprotectant Substances in the Freezing Tolerance of Alfalfa in Cold, Dry Conditions

Abstract: Background: Freezing temperatures are a limiting factor hindering the survival of alfalfa (Medicago sativa L.) through winter. Soil drought also damages alfalfa crowns and can affect their regeneration. Therefore, it is important to determine the effects of cold, dry conditions on alfalfa to develop effective water management strategies in winter. Methods: Cold, dry conditions were established in the laboratory and the freezing tolerance of crowns was compared between the alfalfa cultivars ‘WL440HQ’ and ‘ZhaoD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Research has shown that high-chilling-tolerance cultivars accumulated more antioxidants, enzymes and osmoregulation substances in the anti-stress and environment adaption process compared with low-chilling-tolerance cultivars [41,42]. In more detail, the functions of the soluble protein and carbohydrate levels on the improvement in freezing tolerance were validated in sauvignon [43], while the functions of increased proline and carbohydrates under cold stress were also verified in alfalfa [44]. Furthermore, the enhanced chilling tolerance in watermelon achieved via suboptimal temperature acclimation was contributed to by improved photosynthetic adaptability and osmoregulation ability from substances such as proline, soluble sugar and sucrose [45].…”
Section: Antioxidase and Osmoregulation Substances Played Important R...mentioning
confidence: 92%
“…Research has shown that high-chilling-tolerance cultivars accumulated more antioxidants, enzymes and osmoregulation substances in the anti-stress and environment adaption process compared with low-chilling-tolerance cultivars [41,42]. In more detail, the functions of the soluble protein and carbohydrate levels on the improvement in freezing tolerance were validated in sauvignon [43], while the functions of increased proline and carbohydrates under cold stress were also verified in alfalfa [44]. Furthermore, the enhanced chilling tolerance in watermelon achieved via suboptimal temperature acclimation was contributed to by improved photosynthetic adaptability and osmoregulation ability from substances such as proline, soluble sugar and sucrose [45].…”
Section: Antioxidase and Osmoregulation Substances Played Important R...mentioning
confidence: 92%
“…In these two drought treatments, foliar application with AA decreased the proline content more than that of Ca application. Generally, proline content increases in plants parallel to the rise of damage to cell membranes and the plant tries to mitigate the damage to membranes by increasing the proline level in its tissues (Shinde et al, 2016;Xu et al, 2022).…”
Section: Prolinementioning
confidence: 99%
“…Cold stress damages cell membrane structure, leading to decreased extracellular water potential, increased ion leakage and malondialdehyde (MDA) content, as well as overproduction of reactive oxygen species (ROS) (Ding et al ., 2019; Qi et al ., 2018). Plants have evolved various physiological mechanisms to alleviate damage caused by cold stress, which promote the accumulation of osmoregulatory substances and improve the activity of antioxidant enzymes (Hoermiller et al ., 2022; Wang et al ., 2020; Xu et al ., 2022b). The accumulation of dehydrins and osmotic regulating substances, such as soluble sugars, soluble proteins, betaine and proline, helps to reduce osmotic pressure and stabilize cell membranes, thus improving plant tolerance to cold stress (Feng et al ., 2013; Hayashi et al ., 1997; Hoermiller et al ., 2022; Meena et al ., 2019; Xin and Browse, 2010).…”
Section: Introductionmentioning
confidence: 99%